2006
DOI: 10.1124/mol.106.030601
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Central Nervous System-Active Valproic Acid Constitutional Isomers, Cyclopropyl Analogs, and Amide Derivatives on Neuronal Growth Cone Behavior

Abstract: Valproic acid (VPA) is an effective antiepileptic drug with an additional activity for the treatment of bipolar disorder. It has been assumed that both activities arise from a common target. At the molecular level, VPA targets a number of distinct proteins that are involved in signal transduction. VPA inhibition of inositol synthase reduces the cellular concentration of myo-inositol, an effect common to the mood stabilizers lithium and carbamazepine. VPA inhibition of histone deacetylases activates Wnt signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 34 publications
2
31
0
Order By: Relevance
“…There is a set of evidence that considers the neurotrophic factors as the most relevant adapted mediators after chronic lithium exposure. This is consistent with the ability of lithium to protect cells promoting anti-apoptotic paths, and to inhibit the collapse of sensory neuron growth cones and increase the growth cone area along with other mood stabilizers (valproic acid and carbamazepine) [82] . Intriguingly, this event has been reported to be sensitive to disruption of the inositol orchestration [83] .…”
Section: Resultssupporting
confidence: 61%
“…There is a set of evidence that considers the neurotrophic factors as the most relevant adapted mediators after chronic lithium exposure. This is consistent with the ability of lithium to protect cells promoting anti-apoptotic paths, and to inhibit the collapse of sensory neuron growth cones and increase the growth cone area along with other mood stabilizers (valproic acid and carbamazepine) [82] . Intriguingly, this event has been reported to be sensitive to disruption of the inositol orchestration [83] .…”
Section: Resultssupporting
confidence: 61%
“…Finally, some of the neuroprotective effects of VPA may result from its effects on mitogen-activated protein kinase/extracellular signal-regulated kinase signaling (5,18), which modulates processes such as neuronal differentiation, neuronal survival, and long-term neuroplasticity. In addition to these effects, we have previously shown that prolonged VPA treatment attenuates inositol-(1,4,5)-trisphosphate (InsP 3 ) signaling (12,50,62) using the eukaryotic model system Dictyostelium discoideum, and this effect also occurs in primary rat dorsal root ganglia neurons (12,62). These data support a role for VPA in the inositol depletion theory of bipolar disorder drug action as proposed by Berridge et al (3).…”
supporting
confidence: 69%
“…First, propylisopropylacetic acid (PIA), a specific inhibitor of myo-inositol synthesis (Shimshoni et al, 2007), has a similar effect on chemotaxis to lithium (Fig. 1B).…”
Section: Research Reportmentioning
confidence: 99%